Marketing Management and Corporate Comprehensive Profitability with Leverage Moderation : South East Asia Evidence - Marjukah, Anis; Sri Nugroho, Arif Julianto; Haris, Abdul; Kusuma, Marhaendra; Singh, Sanju Kumar (Universitas Islam Kadiri, 2025)
This study aims to demonstrate the influence of marketing management on corporate comprehensive profitability and the moderating role of leverage in the relationship. Data were collected from 5,272 firm-years from 1,318 sample companies in Southeast Asia for the period 2021-2024. Moderated regression analysis was used to analyze the data. The results demonstrate that a more optimal marketing management role leads to greater corporate comprehensive profitability, and pressure from creditors, as indicated by a higher leverage ratio, strengthens the influence of marketing management on corporate comprehensive profitability. The novelty of this study lies in the use of various proxies to measure marketing management variables and the novelty of the model for testing the moderating role of leverage in marketing management's influence on corporate comprehensive profitability.